Good Practice Of Special Education In Japan - Sujarwanto (Pendidikan Dasar, 2007)
To achieve a success in the implementation of special education in Indonesia, good practices of Japanese system are worth adapting. Although the two countries are pursuing different models of special education, five main characteristics of the Japanese system are possibly adapted. They include classroom activities, networking, health issues, in-service training and school cooperation with hospitals.